SYNTHESIS AND EVALUATION OF THE BIOLOGICAL ACTIVITY FOR SOME OF CARBAZOLE DERIVATIVES - Al- Sultani, Khitam T A (Al-Nahrain Journal of Science, 2010)
This research includes preparing of some carbazole derivatives .The (3,6-Disulfonylchloride-9H- carbazole (1) was achieved by the reaction of carbazole with chloro sulfonic acid incold condition, reaction of compound (1) with sodium azide in acetone as a solvent to give(3,6-Disulfonyl azide-9H- carbazole) (2), then reaction of compound (2) with different phosphineand phosphate compounds(1mole and 2 mole) yielded the (3,6-Disulfonyl -6- azide-3-(phosphine orphosphate imine)-9H- carbazole) derivatives (3-8) and (3,6-Disulfonyl (phosphine or phosphateimine)-9H- carbazole) derivatives respectively (9-14).Some of physical properties have determinedfor the prepared compound, and identified by spectral methods (FTIR, 1H-NMR, 13C-NMR),furthermore evaluation of the biological activity for some of the prepared compounds on two typeof bacteria Bacillus and E.Coli.